Marketing strategies in cross-border tourist destinations - Pahor Žvanut, Alenka (Academica turistica, 2023)
The basic principle of the operation of a tourist destination as a system of connected stakeholders is the creation of new value that is reflected in the creation of added value for participants in the business process. To create added value, stakeholders need to strategically plan and manage their marketing function. A systematic quali-tative review of the latest current literature (last ten years) is carried out in the field of introducing marketing strategies into the wider strategy of developing cross-bordertourist destinations. The selected databases were Web of Science and Scopus. We found that cross-border tourist destinations do not take systematic approaches to introduce marketing strategies, but rather identify themselves as a part of broader development strategies of cross-border areas. In rare cases, stand-alone brands are formed to help destinations consolidate their market position and exploit the potential of two or more cross-border destinations at the same time. Despite identifying different synergistic effects and understanding the importance and benefits of integration and coopetition, marketing strategies in cross-border tourist destinations are not yet standardized business practice. The review article contributes to show-casing the important role of cross-border marketing strategies in tourism and paves the way for more detailed research on the topic in the future.
Keywords: cross-border; čezmejna območja; marketing; marketing strategy; strategy; tourism; tourist destination; turistične destinacije; turizem